ANALISIS PERAWATAN MESIN DRINKING WATER DENGAN METODE RELIABILITY CENTERED MAINTENANCE (RCM) - Solehudin, Agus; Mulyadi, Cecep Deni; Fhaizal, Mohamad Agus; Fadhal (LPPM Universitas Sangga Buana, 2024)
The company where author currently work is at PT Angkasa Pura Solusi a subsidiary of PT Angkasa Pura II (Persero) Soekarno-Hatta International Airport, the author in Water Treatment unit as a senior technician. This unit is responsible for operating, maintaining, and repairing clean water distribution equipment to terminals and buildings at Soekarno-Hatta Airport as well as overcoming disturbances, repairing, replacing, and maintain the equipment at Soekarno-Hatta International Airport in accordance with applicable regulations. One of the responsibilities is the maintenance of Drinking Water Machine equipment, for current conditions maintenance of Drinking Water Machine equipment is only carried out if there are complaints of problems by telephone. For scheduled or planned maintenance has been carried out but is still not effective. The result is that the tool experiences a short lifetime on the supporting components of the Drinking Water Machine tool which makes the tool unable to operate properly and leads to budget overruns because they have to continue to replace damaged spare parts components so that the tool can operate optimally at performance figures above 90%, in addition to the impact caused by equipment operational downtime due to lack of preparation when the Drinking Water Machine tool must be repaired. For this reason, the author makes a maintenance analysis of the Drinking Water Machine with the Reliability Centered Maintenance (RCM) method, from this method it will be known what components of the Drinking Water Machine are often damaged or malfunctioned.